Manfaat Jus Mentimun Dalam Menjaga Kestabilan Tekanan Darah Masyarakat Di Kelurahan Hepuhulawa - Djamaluddin, Nurdiana; Dumar, Bergita (Bengkulu Institute, 2025)
Abstract Hypertension is one of the non-communicable diseases that are often found in society and is the main cause of cardiovascular complications. High blood pressure or known as Hypertension is an abnormal condition where this often occurs in the elderly, where in general the older a person is, the greater the risk of Hypertension. One form of how to do this is through education and implementation of a healthy lifestyle, including consumption of natural ingredients such as cucumber juice (Cucumis sativus), as one of the promotive and preventive approaches that can be done at the community level. This community service activity aims to increase public knowledge and awareness of the benefits of cucumber juice as a natural alternative in stabilizing blood pressure. Keywords: Blood Pressure, Hypertension, Cucumber Juice